How Do Anchors' Characteristics Influence Consumers' Behavioural Intention in Livestream Shopping? A Moderated Chain-Mediation Explanatory Model - Zhu, Liangjie; Li, Huiyao; Nie, Kun; Gu, Chunmei (Frontiers in Psychology, 2021)
Livestream shopping is becoming the focus of current practice, while theoretical research on it is still in the initial stage. Thus, from the para-social interaction (PSI) theory perspective, while considering the characteristics of consumer online interaction propensity, this study focuses on cognitive–affective system theory as an analytical framework to explore internal mechanisms of anchors’ characteristics that influence consumer behavioural intentions in livestream shopping. The study determined that anchors’ physical and social attractiveness and professional ability influence consumers’ intentions to follow the authors’ suggestions and recommend anchors to others during live streams. PSI and affective trust in anchors are the chain-mediation mechanisms. Furthermore, consumers’ online interaction propensity positively moderates the influence of anchors’ characteristics on PSI and plays a moderating role on the whole chain mediation. However, this only affects anchors’ physical and social attractiveness with no effect on anchors’ professional ability. This study advances the theoretical research on livestream shopping and provides practical inspiration for managers to develop more targeted livestream marketing strategies.